Hysteroscopic evaluation of postmenopausal bleeding patients and its correlation with histopathological examination - Mansingh, Sudhir; Dhillon, Atmajit Singh; Sood, Sandeep; Anne, Sirisha; Godi, Prema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Menopause is defined according to WHO as the permanent cessation of menstruation resulting from the loss of ovarian follicular activity. It is defined as uterine bleeding occurring after at least 1 year of amenorrhoea. Considering the high accuracy of hysteroscopy in evaluation of postmenopausal bleeding, the present study was carried out with an aim to evaluate hysteroscopic findings in women with postmenopausal bleeding in order to assess the causes of PMB and to determine their prevalence in our population. Methods: This was a prospective observation study, comprising of total number of 50 postmenopausal women attending gynae OPD at department of obstetrics and gynecology, Command Hospital (CH), Lucknow, Uttar Pradesh. The data obtained for the purpose of study was fed into computer using Microsoft excel 2013 software. Results: A total of 50 women with complaints of postmenopausal bleeding were enrolled in the study. Maximum number of women had achieved menopause between age 46 and 50 years. Hysteroscopy had an accuracy of 94% for detection of polyps. Hysteroscopy had an accuracy of 90% for detection of atrophy. For fibroid, hysteroscopy had an absolute sensitivity, specificity, positive predictive, negative predictive and accuracy value (100%). Conclusions: The findings of present study suggested that hysteroscopy has a useful role in evaluation of postmenopausal bleeding especially in the diagnosis of polyps and fibroids. Given fewer number of cases, the usefulness of hysteroscopy in evaluation of endometrial cancer and hyperplasia could not be established adequately. Further studies on larger number of sample size will help in providing more useful and confirmatory information.